2011
DOI: 10.1111/j.1442-2042.2011.02857.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic promontofixation for pelvic organ prolapse: A 10‐year single center experience in a series of 501 patients

Abstract: Objectives:To assess the long-term outcomes of laparoscopic promontofixation (LP) for the treatment of pelvic organ prolapse (POP). Methods: A total of 501 consecutive patients with POP were included in this prospective study. The patients' mean age was 63.23 (36-90) years, their mean body mass index was 25.14 (15-36) and their mean number of deliveries was 3.3 (0-14). A POP grade Ն3 was diagnosed in 70.4% of the patients and 38.9% of them had a history of abdominal surgery. The patients underwent a Bonney tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…The simple size and the median follow‐up analyzed in this study could be considered the strengths of our paper, considering the existing literature …”
Section: Discussionmentioning
confidence: 98%
“…The simple size and the median follow‐up analyzed in this study could be considered the strengths of our paper, considering the existing literature …”
Section: Discussionmentioning
confidence: 98%
“…9 Hence, having more data concerning the efficacy and safety of laparoscopic sacro colpopexy, such as that provided by the Bacle et al 2 study, may prove helpful for surgeons. However, the technical challenges associated with laparoscopy may prevent some surgeons from using this approach: specifically, laparoscopic suturing remains a considerable barrier, as well as concern for avoiding the presacral vessels during dissection of the anterior longitudinal ligament.…”
Section: News and Viewsmentioning
confidence: 96%
“…Although many experts seem to agree that location and depth of injection has little effect on efficacy, data are available to both confirm and dispute these opinions. [1][2][3] Manecksha et al 4 have reported a clinical trial that used 500 U abobotulinumtoxinA in a setting of refractory idiopathic detrusor overactivity (IDO), where patients were randomized to receive either trigone-sparing bladder injections or bladder injections that included the trigone. The group of patients who received the trigone and bladder injections had a better overactive bladder symptom score (OABSS) at 6 weeks after treatment compared with the trigone-sparing group (P = 0.03).…”
Section: Arun Sahai and Prokar Dasguptamentioning
confidence: 99%
See 2 more Smart Citations